Influence of Wall Porosity and Surfaces Roughness on the Steady Performance of an Externally Pressurized Hydrostatic Conical Bearing Lubricated by a Rabinowitsch Fluid - A. Walicka; E. Walicki; P. Jurczak; J. Falicki (International Journal of Applied Mechanics and Engineering, 2017)
In the paper, the influence of both the bearing surfaces roughness as well as porosity of one bearing surface on the pressure distribution and load-carrying capacity of a curvilinear, externally pressurized, thrust bearing is discussed. The equations of motion of a pseudo-plastic Rabinowitsch fluid are used to derive the Reynolds equation. After general considerations on the flow in a bearing clearance and in a porous layer using the Morgan-Cameron approximation and Christensen theory of hydrodynamic lubrication with rough bearing surfaces the modified Reynolds equation is obtained. The analytical solution is presented; as a result one obtains the formulae expressing the pressure distribution and load-carrying capacity. Thrust radial and conical bearings, externally pressurized, are considered as numerical examples.